2016
DOI: 10.4038/cjsbs.v44i2.7350
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic polymorphism in two North American reindeer lichens: Cladonia arbuscula and C. rangiferina

Abstract: Cladonia arbuscula and C. rangiferina are two reindeer lichen species, which are widely distributed in northern climates and have not been shown to be monophyletic. The wide species distribution may suggest an outcrossing reproductive life style, which may contribute to paraphyly and success of these two species. The current study examined the genetic diversity of mycobiont ascospore colonies within and between apothecia of two species, C. rangiferina and C. arbuscula s. l. using Randomly Amplified Polymorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Our data indicated greater diversity in C. mitis than in C. stellaris , as some authors have already suggested. Athukorala et al (2016) pointed out the intraspecific variation in the ITS rDNA of all reindeer lichens (except for C. stellaris ). Other studies focused exclusively on C. mitis (as C. arbuscula s.l.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data indicated greater diversity in C. mitis than in C. stellaris , as some authors have already suggested. Athukorala et al (2016) pointed out the intraspecific variation in the ITS rDNA of all reindeer lichens (except for C. stellaris ). Other studies focused exclusively on C. mitis (as C. arbuscula s.l.)…”
Section: Discussionmentioning
confidence: 99%
“…Other studies focused exclusively on C. mitis (as C. arbuscula s.l.) to highlight the elevated genetic variation in the species (Piercey‐Normore et al, 2010; Athukorala et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, C. arbuscula and C. mitis occur in similar habitats, but C. arbuscula usually exists within a narrower range of environmental variables than C. mitis . Due to their greater genetic variability, C. arbuscula and C. mitis might have an adaptive advantage over C. rangiferina (Athukorala et al 2015). Although our studied lichens originate from different locations, our results justify differences between these species in respect of their characteristic habitat features.…”
Section: Discussionmentioning
confidence: 99%
“…spp. The ground layer is mostly covered by a mosaic of reindeer lichens (mainly Cladonia arbuscula/mitis, C. rangiferina/stygia (see References [39,40] for discussion of nomenclature), and C. stellaris-collectively termed "reindeer lichens" and feather mosses (Pleurozium schreberi, Hylocomium splendens, and Ptilium crista-castrensis).…”
Section: Study Areamentioning
confidence: 99%